FEATURES OF APPLICATION OF THE MULTIPLE DIAGNOSTIC ANALYSIS IN MODERN ECONOMIC CONDITIONS - T. Barsova; A. Sazonov; V. Proskuryakov (Вестник университета)
In article it is proved that one of the methods which are most often applied in the course of the analysis and planning of production activity of the enterprises is economic diagnostics. Relevance of economic diagnostics at the present stage is connected from subjects by a possibility of its application in the conditions of incomplete information for identification of problems of development and perspective ways of their decision. Main types of economic diagnostics of the enterprise are given, and also possible analytical methods for the solution of problems of economic diagnostics are presented.